Composition and Diversity of Dragonflies (Odonata) in Several Habitat Types in Lumajang Regency, East Java Province, Indonesia - Susanto, Muhamad Azmi Dwi; Millah, Najmatul; Leksono, Amin Setyo; Gama, Zulfaidah Penata (Journal of Tropical Biodiversity and Biotechnology, 2024)
Lumajang is one of the regency in East Java Province that has various types of freshwater ecosystems and have great potential as habitats for various insects, especially dragonflies. Dragonflies are insects that mostly live aquatically, so their existence is highly dependent on the condition of aquatic ecosystems. This study aims to compare the composition and diversity of dragonfly species in various habitat types in Lumajang. The study was conducted in lentic and lotic ecosystems in Lumajang. The method used was the Visual Encounter Survey (VES) technique adapted from the sweeping net. The data analysis used to determine differences in dragonfly species composition was the Bray-Curtis similarity analysis, while diversity analysis was conducted using the Shannon-Wiener index. This study recorded 29 species from seven families, including seven endemic dragonfly species found only on several islands in Indonesia. In the analysis of the Shannon-Wiener diversity index, the results show that in all research locations have a value of H'= 1.07‒2.11, where the Rice Field habitat is the location with the highest value among other locations, with a value of H' = 2.11. The similarity analysis of dragonfly species composition using Bray Curtis similarity showed that it was divided into three groups. The composition of dragonflies found in several habitats in Lumajang is different, which can be influenced by many factors such as site elevation, habitat type (lentic or lotic), and habitat condition, as well as several other factors such as microclimate and vegetation (related to food availability).